Controls of sea–air O2 and CO2 exchanges along the Patagonian shelf-break: the role of temperature and phytoplankton communities - Luísa M. Garcia; Iole Beatriz M. Orselli; Virginia Maria Tavano; Carlos Rafael B. Mendes; Carlos Alberto E. Garcia; Rosane G. Ito; Catherine Goyet; Rodrigo Kerr (Progress in Oceanography, 2026)

The invasion history of Ambrosia psilostachya (Asteraceae) in Italy: first record and distribution over more than one century - Chiara Montagnani; Rodolfo Gentili; Gerhard Karrer; Sarah Caronni; Alicia Teresa Rosario Acosta; Michele Adorni; Alessandro Alessandrini; Nicola Maria Giuseppe Ardenghi; Gabriella Buffa; Fabrizio Bartolucci; Alessandra Belisario; Fabrizio Bonali; et al. (Plant Biosystems, 2025)

Sea-air CO2 exchanges, pCO2 drivers and phytoplankton communities in the southwestern South Atlantic Ocean during spring - Rodrigo Kerr; Thiago Monteiro; Iole Beatriz M. Orselli; Virginia Maria Tavano; Carlos Rafael B. Mendes (Marine Chemistry, 2024)

Spatiotemporal variability of dissolved inorganic macronutrients along the northern Antarctic Peninsula (1996–2019) - Thiago Monteiro; Sian F. Henley; Ricardo César Gonçalves Pollery; Carlos Rafael Borges Mendes; Mauricio Mata; Virginia Maria Tavano; Carlos Alberto Eiras Garcia; Rodrigo Kerr (Limnology and Oceanography, 2023)
The northern Antarctic Peninsula is a key region of the Southern Ocean due to its complex ocean dynamics, distinct water mass sources, and the climate‐driven changes taking place in the region. Despite the importance of macronutrients in supporting strong biological carbon uptake and storage, little is known about their spatiotemporal variability along the northern Antarctic Peninsula. Hence, we explored for the first time a 24‐year time series (1996–2019) in this region to understand the processes involved in the spatial and interannual variability of macronutrients. We found high macronutrient concentrations, even in surface waters and during strong phytoplankton blooms. Minimum concentrations of dissolved inorganic nitrogen (DIN; 16 μ mol kg −1 ), phosphate (0.7 μ mol kg −1 ), and silicic acid (40 μ mol kg −1 ) in surface waters are higher than those recorded in surrounding regions. The main source of macronutrients is the intrusions of Circumpolar Deep Water and its modified variety, while local sources (organic matter remineralization, water mass mixing, and mesoscale structures) can enhance their spatiotemporal variability. However, we identified a depletion in silicic acid due to the influence of Dense Shelf Water from the Weddell Sea. Macronutrient concentrations show substantial interannual variability driven by the balance between the intrusions of modified Circumpolar Deep Water and advection of Dense Shelf Water, which is largely modulated by the Southern Annular Mode (SAM) and to some extent by El Niño‐Southern Oscillation (ENSO). These findings are critical to improving our understanding of the natural variability of this Southern Ocean ecosystem and how it is responding to climate changes.

Cryptophytes: An emerging algal group in the rapidly changing Antarctic Peninsula marine environments - Carlos Rafael Borges Mendes; Raul Rodrigo Costa; Afonso Ferreira; Bruno Jesus; Virginia Maria Tavano; Tiago Segabinazzi Dotto; Miguel Costa Leal; Rodrigo Kerr; Carolina Antuarte Islabão; Andréa de Oliveira da Rocha Franco; Mauricio M. Mata; Carlos Alberto Eiras Garcia; et al. (Global Change Biology, 2023)
The western Antarctic Peninsula (WAP) is a climatically sensitive region where foundational changes at the basis of the food web have been recorded; cryptophytes are gradually outgrowing diatoms together with a decreased size spectrum of the phytoplankton community. Based on a 11‐year (2008–2018) in‐situ dataset, we demonstrate a strong coupling between biomass accumulation of cryptophytes, summer upper ocean stability, and the mixed layer depth. Our results shed light on the environmental conditions favoring the cryptophyte success in coastal regions of the WAP, especially during situations of shallower mixed layers associated with lower diatom biomass, which evidences a clear competition or niche segregation between diatoms and cryptophytes. We also unravel the cryptophyte photo‐physiological niche by exploring its capacity to thrive under high light stress normally found in confined stratified upper layers. Such conditions are becoming more frequent in the Antarctic coastal waters and will likely have significant future implications at various levels of the marine food web. The competitive advantage of cryptophytes in environments with significant light level fluctuations was supported by laboratory experiments that revealed a high flexibility of cryptophytes to grow in different light conditions driven by a fast photo‐regulating response. All tested physiological parameters support the hypothesis that cryptophytes are highly flexible regarding their growing light conditions and extremely efficient in rapidly photo‐regulating changes to environmental light levels. This plasticity would give them a competitive advantage in exploiting an ecological niche where light levels fluctuate quickly. These findings provide new insights on niche separation between diatoms and cryptophytes, which is vital for a thorough understanding of the WAP marine ecosystem.

The invasion history of Elodea canadensis and E. nuttallii (Hydrocharitaceae) in Italy from herbarium accessions, field records and historical literature - Fabrizio Buldrini; Giovanna Pezzi; Martina Barbero; Alessandro Alessandrini; Lucia Amadei; Sebastiano Andreatta; Nicola Maria Giuseppe Ardenghi; Stefano Armiraglio; Simonetta Bagella; Rossano Bolpagni; Ilaria Bonini; Daniela Bouvet; et al. (Biological Invasions, 2023)
We analysed the invasion history of two North American macrophytes ( Elodea canadensis and E. nuttallii ) in Italy, through an accurate census of all available herbarium and field records, dating between 1850 and 2019, and a rich literature collection describing the initial introduction and naturalisation phase that supports the results obtained by the occurrence records. Elodea canadensis arrived in Italy before 1866 and had two invasion phases, between the 1890s and 1920s and between the 1990s and 2000s; E. nuttallii , probably arrived in the 1970s, started invading in 2000 and the invasion is still ongoing. Botanical gardens and fish farming played a crucial role in dispersal and naturalisation of both species. The current invasion range of both species is centred in northern Italy, with scattered occurrences of E. canadensis in central and southern regions. River Po represents a dispersal barrier to the Mediterranean region and a strategic monitoring site to prevent the invasion in the peninsula. The study detects differences in the niches of the two species during the introduction and naturalisation phase and a habitat switch occurred after 1980 in E. canadensis and after 2000 in E. nuttallii , during their expansion phases. For E. canadensis the switch corresponds to the second invasion round. Further research can clarify whether the second invasion round is due to confusion of the recently introduced E. nuttallii with E. canadensis , to a cryptic introduction of a new genotype, to post-introduction evolution, or just to an increased scientific interest in biological invasions.

Biomonitoring of urinary metals in athletes according to particulate matter air pollution before and after exercise - Sabina Cauci; Michael Tavano; Francesco Curcio; Maria Pia Francescato (Environmental Science and Pollution Research, 2022)

Dynamics of an intense diatom bloom in the Northern Antarctic Peninsula, February 2016 - Raul Rodrigo Costa; Carlos Rafael Borges Mendes; Virginia Maria Tavano; Tiago Segabinazzi Dotto; Rodrigo Kerr; Thiago Monteiro; Clarisse Odebrecht; Eduardo Resende Secchi (Limnology and Oceanography, 2020)
Diatoms are considered the main base of the Southern Ocean food web as they are responsible for more than 85% of its annual primary production and play a crucial role in the Antarctic trophic structure and in the biogeochemical cycles. Within this context, an intense diatom bloom reaching > 45 mg m −3 of chlorophyll a was registered in the Northern Antarctic Peninsula (NAP) during a late summer study in February 2016. Given that nutrient concentrations and grazing activities were not identified here as limiting factors on the bloom development, the aim of this study was to evaluate the effect of water column structure (stability and upper mixed layer depth) on the phytoplankton biomass and composition in the NAP. The diatom bloom, mainly composed by the large centric Odontella weissflogii (mostly > 70 μ m in length), was associated with a local ocean carbon dioxide uptake that reached values greater than −60 mmol m −2 d −1 . We hypothesize that the presence of a vertically large water column stability barrier, just below the pycnocline, was the main driver allowing for the development of the intense diatom bloom, particularly in the Gerlache Strait. Contrarily, a shift from diatoms to dinoflagellates (mainly Gymnodiniales μ m) was observed associated with conditions of a highly stable thin layer. The results suggest that a large fraction of this intense diatom bloom is in fast sinking process, associated with low grazing pressure, showing a crucial role of diatoms for the efficiency of the biological carbon pump in this region.

Pigment-based chemotaxonomy of phytoplankton in the Patos Lagoon estuary (Brazil) and adjacent coast - Carlos Rafael Borges Mendes; Clarisse Odebrecht; Virginia Maria Tavano; Paulo Cesar Abreu (Marine Biology Research, 2017)

Shifts in the dominance between diatoms and cryptophytes during three late summers in the Bransfield Strait (Antarctic Peninsula) - Carlos Rafael Borges Mendes; Virginia Maria Tavano; Miguel Costa Leal; Márcio Silva de Souza; Vanda Brotas; Carlos Alberto Eiras Garcia (Polar Biology, 2013)